Gastroenterologists Adherence to Tumor Necrosis Factor Antagonist Combination Therapy in Inflammatory Bowel Disease - Abdullah, Israa; Alhendi, Ghadeer; Alhadab, Anwar; Alasfour, Hajer; Shehab, Mohammad (Frontiers in Medicine, 2021)
Abstract: Introduction: Tumor necrosis factor antagonist (anti-TNF) therapy is being used for the management of moderate to severe inflammatory bowel disease (IBD). Anti-TNF combination therapy, especially for Inflixmab, has been shown to reduce immunogenicity, improve treatment success rate and patient outcomes. We evaluated factors associated with gastroenterologists adherence to anti-TNF combination therapy. Methods: A retrospective cohort study was performed to evaluate the adherence of gastroenterologists (n=14) , at an inflammatory bowel disease center, to anti-TNF combination therapy. Records of patients who received Infliximab (n=137) or adalimumab (n=152) were obtained and their ordering physicians data was analysed. Results: The proportion of patients on infliximab and adalimumab combination therapy in the young gastroenterologists group was higher than those in the senior gastroenterologists group (P<0.001). Gastroenterologists with interest in inflammatory bowel disease (IBD interest group) had also more proportion of patients on adalimumab combination therapy compared to gastroenterologists with no interest in IBD (non-IBD interest group)(P<0.001). Gastroenterologists who were both young and have interest in IBD had more proportion of patients on combination therapy than those who were senior or had no interest in IBD for both infliximab and adalimumab (P<0.001). The IBD interest group was also requesting more antidrug antibody level tests than those in the non-IBD interest group (P<0.001). Conclusion: Young gastroenterologists are more likely to prescribe anti-TNF infliximab and adalimumab combination therapy than senior gastroenterologists. In addition, gastroenterologists with IBD interest are more likely to prescribe adalimumab combination therapy than gastroenterologists with no IBD interest. Moreover, young gastroenterologists who have interest in IBD are more likely to prescribe both infliximab and adalimumab combination therapy than senior gastroenterologists or those with no IBD interest. In addition, gastroenterologists with IBD interest requested more anti-TNF serum drug concentrations and antidrug antibody level tests than those with no IBD interest.